Onomatope dalam Komik Nusa Five Volume 1 karya Sweta Kartika - Muhammad Nurun Shofi; Bram Denafri (Faculty of Languages and Arts, Universitas Negeri Padang, 2021)
This study aims to describe the onomatopoeic form in the Comic Nusa Lima volume 1 by Sweta Kartika. The theory used is the onomatopoeic form theory proposed by Sudaryanto (1989) and the onomatopoeic meaning theory proposed by Ulman (2011). This research is descriptive research. Data collection using the observation method. The technique used in the data collection stage is a non-participant technique. Researchers observed and recorded data in the form of words containing onomatopoeic elements contained in the comic Nusa Five by Sweta Kartika. The data analysis method used in this research is the equivalent method and the method of agih. The results of this study found that the onomatopoeic form of the root word was divided into one syllable and bisilabel. In the reduplication category, the researchers found full repetitions and three repetitions (trilingga). The results of this study concluded that the use of onomatopoeia in the form of reduplication was dominant in Nusa Five Comics.